Developing Student Motivation through The Use of Authentic Materials in Practical Lessons - Kholiyorov, Bunyod (Researchparks Publishing, 2025)
Various pedagogical approaches are currently being implemented in the field-oriented teaching of English within non-philological higher educational institutions. However, this process predominantly emphasizes methodological aspects, often neglecting the psychological state of students and their perception of the language material. Yet, in the educational process, students' psychological well-being and their intrinsic motivation to master the subject serve as critical factors in ensuring lesson effectiveness. Unlike learners studying English for general purposes, those engaged in English for specific purposes (ESP) develop their interest based on their professional aspirations, recognizing the direct relevance of the language to their future careers and the necessity of familiarizing themselves with global best practices in their field. Therefore, English instructors must emphasize the significance of language proficiency within students' respective dis-ciplines. Moreover, educators should adopt a holistic approach, acting not only as instructors but also as mentors who are genuinely invested in students' academic and professional growth. The strategic integration of authentic materials fosters a realistic professional environment within the learning process, enhancing students' linguistic competence and preparing them to overcome language barriers in their future careers. Consequently, this study explores the role of authentic ma-terials in fostering student motivation within ESP instruction, highlighting their effectiveness as a non-traditional ped-agogical approach. Additionally, the study examines the importance of a student-centered teaching paradigm, the culti-vation of a supportive learning atmosphere, and the dismantling of stereotype-based barriers in language acquisition.